2019
DOI: 10.1021/acs.jpclett.8b03406
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Extremely Efficient Sensitization of Yb3+Luminescence in CsPbCl3 Nanocrystals

Abstract: Rare earth ion (RE3+)-doped inorganic CsPbX3 (X = Cl or Cl/Br) nanocrystals have been presented as promising materials for applications in solar-energy-conversion technology. An extremely efficient sensitization of Yb3+ luminescence in CsPbCl3 nanoparticles (NCs) was very recently demonstrated where quantum cutting is responsible for the performance of photoluminescence quantum yields over 100% (Nano Letters2018183792). In the present work, based on the cubic phase of inorganic perovskite, we seek to obtain at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 42 publications
(75 reference statements)
2
49
1
Order By: Relevance
“…It was suggested that this defect forms a shallow state below the conduction band minimum, facilitating picosecond nonradiative energy transfer from the photoexcited host NC to two Yb 3+ ions simultaneously, yielding quantum cutting 22 . Later, theoretical studies extended the mechanistic insight 36 . They suggested that the two Yb 3+ dopants are excited in a concerted manner through nonradiative energy transfer from the PbCl 6 octahedra closest to the two Yb 3+ dopants (see Fig.…”
Section: Quantum Cutting and Band Gap Tuningmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that this defect forms a shallow state below the conduction band minimum, facilitating picosecond nonradiative energy transfer from the photoexcited host NC to two Yb 3+ ions simultaneously, yielding quantum cutting 22 . Later, theoretical studies extended the mechanistic insight 36 . They suggested that the two Yb 3+ dopants are excited in a concerted manner through nonradiative energy transfer from the PbCl 6 octahedra closest to the two Yb 3+ dopants (see Fig.…”
Section: Quantum Cutting and Band Gap Tuningmentioning
confidence: 99%
“…They suggested that the two Yb 3+ dopants are excited in a concerted manner through nonradiative energy transfer from the PbCl 6 octahedra closest to the two Yb 3+ dopants (see Fig. 3c) 36 .…”
Section: Quantum Cutting and Band Gap Tuningmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Nonetheless, the upper limit of the emission wavelength still remains below 1.0 μm, which greatly restricts the particularly interesting applications of these materials in optoelectronic and photonic devices working in the NIR such as telecommunication, light-emitting diodes, and lasers. [22][23][24] Unlike Yb 3+ -doped CsPbCl3, which exhibits an extremely intense Yb 3+ NIR emission at ~1.0 μm through a quantumcutting effect, [17,19,25] other NIR luminescent lanthanide ions (Ln 3+ ), such as Er 3+ , Nd 3+ and Ho 3+ unexpectedly show negligible emission. This anomalous phenomenon is likely related to the relatively high redox potential of the Yb 3+ /Yb 2+ pair which allows for a transient internal redox mechanism within the CsPbCl3 matrix releasing enough energy to excite two Yb 3+ ions.…”
Section: Introductionmentioning
confidence: 99%
“…In lead-based systems, doping with Ln 3+ proceeds through the substitution of three Pb 2+ for every two incorporated lanthanides. 96,118 To maintain a charge balance, a Pb 2+ vacancy (VPb) is also introduced. The most energetically favourable configuration of the resulting defect complex (Ln 3+ -VPb-Ln 3+ ) is shown in (Figure 5E).…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…In a following study, Li et al modelled this quantum cutting phenomenon and explained it in light of a higher density of states at the CB edge featured by the Pb 2+ sitting close to the Yb 3+ ions; this favours strong localized absorption and prompt transfer of the energy to the two nearby Yb 3+ . 118 Ln 3+ -doped lead-based perovskite SNCs were also used for preparing with-light emitting diodes, wherein blueemitting GaN chips where coated with polymeric dispersions of, e.g., CsPbCl3:Ce 3+ ,Eu 3+121 or…”
Section: Conflicts Of Interestmentioning
confidence: 99%